TINGKAT PENGETAHUAN PASIEN TENTANG PERAWATAN GASTRITIS DI RS UMUM BANGKATAN BINJAI TAHUN 2016 - Siregar, Ilham Syahputra (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2016)
Gastritis is an inflammation that affects the gastric mucosa. This inflammation can result in coagulation of the gastric mucosa until the release of the superficial mucosal epithelium is the most important cause of digestive tract disorders. Epithelial release will stimulate the onset of the inflammatory process in the stomach.Gastritis or dyspepsia or a term known by the community as an ulcer or stomach disease is a collection of symptoms that are felt as pain, especially in the pit of the stomach, people who are attacked by this disease are usually often nausea, vomiting, feeling full and feeling uncomfortable. The cause of gastritis is the use of non-steroidal anti-inflammatory drugs such as aspirin, mafenamat acid, in large quantities, excessive alcohol consumption, lots of smoking, chemotherapy testing, severe stress, consumption of oral chemicals that are acid-base and ischemic shock. The purpose of this study is to determine the level of patient's knowledge about the treatment of gastritis (ulcer).The research method used is descriptive quantitative method, taking samples using accidental sampling techniques. As many as 30 people with questionnaire data collection instruments. The data obtained are grouped based on the level of patient's knowledge of gastritis. Based on the level of knowledge of patients about gastritis treatment, there were 13 people (43%), quite 12 people (40%), and less as many as 5 people (17%) so that it can be concluded that the patient's knowledge of gastritis treatment at Binjai City General Hospital is classified well. But it is not applied in everyday life.Keywords: Patient Knowledge, Gastritis, Gastritis Treatment.